PROFIL EKONOMI RUMAH TANGGA SUPIR ANGKUTAN ANTAR KOTA PEKANBARU-BANGKINANG - Titin Fatimah; Ashaluddin Jalil (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This study aims to determine the economic profile of domestic inter-city transport driver Pekanbaru-Bangkinang and tofind out how what is being done inter-city transport drivers to meet the economic needs of the family. Population of this research is all driver sub-urban which status and ownership of the vehicle is a rental that has been married as many as 11 sub-urban transport drivers.This study used quantitative descriptive method with quantitative and qualitative data analysis. The collection of data through observation and questionnaires.The theory used is the theory of economic sociology, the theory of a survival strategies and the theory of patron-client. The results can be generalized that the income of the transport drivers suburban still being sufficient for household so that they meet the needs of families with pursuing a strategy of how to get a lot of passengers, and by working together with his wife for earning money for family life, as his wife opened a small shop at home and using a strategy of active, passive strategies, and networking strategies for survival. Home ownership status generally is proprietary with the physical condition ofthe househas been largely permanent which have private wells and generally have been using an electric kilometer. When family get illness usually taken to the nearest health centers and clinics, while in education, all children can educated although not up to the college level.Keywords: household economy , survival strategies, minibus transport drivers